Open Source Software Governance: A Case Study Evaluation of Supply Chain Management Best Practices - Harutyunyan, Nikolay; Riehle, Dirk (56th Hawaii International Conference on System Sciences, HICSS '23, 2023)
Corporate open source governance aims to manage the increasing use of free/libre and open source software (FLOSS) in companies. To avoid the risks of the ungoverned use, companies need to establish processes addressing license compliance, component approval, and supply chain management (SCM). We proposed a set of industry-inspired best practices for supply chain management organized into a handbook. To evaluate the handbook, we ran a one-year case study at a large enterprise software company, where we performed semi-structured interviews, workshops, and direct observations. We assessed the initial situation of open source governance, the implementation of the proposed SCM best practices, and the resulting impact. We report the results of this study by demonstrating and discussing the artifacts created while the case study company implemented the SCM-focused governance process. The evaluation case study enabled the real-life application and the improvement of the proposed best practices.<br
Keywords: Best practices; case study research; corporate open-source governance; open-source software; supply chain management; software supply chains